THE FAILURE OF PEACEBUILDING IN SOMALIA: THE 'MYTH' OF THE NATION-STATE - IGBA, Ajogwu Samuel; WIELENGA, Cori (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
There is a growing consensus in International Relations that the sovereign nation state, particularly in sub-Saharan Africa, is a ‘myth’ because of the several nations that can be found within one sovereign entity, made so by the Berlin conference of 1885 that partitioned Africa. Regardless of this consensus, international peacebuilding theory and practice is biased towards maintaining these sovereign arrangements. Through a decolonial lens, peacebuilding in Somalia is explored as an example of how these biases affect peace in a multiethnic, multiclan, and diverse society.